Indicators of Students’ Intention to Use Massive Open Online Courses for Academic Purposes - Tahiru, Mukaramatu; Kamalludeen, Rosemaliza (KIPERONLINE ACADEMIC, 2018)
Massive Open Online Courses (MOOCs) have a considerable potential impact on teaching, learning, and traditional higher educational structures, according to many types of research. Several higher education institutions either through the specific development of MOOCs or the integration of existing MOOCs into their curriculum are swiftly implementing them on their campuses. To examine the MOOCs phenomenon more closely, this study explored the significant difference between MOOCs users and non-users in their intention to use MOOCs for academic purposes. It again explored the influence of awareness knowledge, how-to knowledge, perceived usefulness, actual usage, and attitude on intention to use MOOCs for academic purposes. The sample consisted of 190 postgraduate students. The analysis procedure made use of independent sample t-test and multiple regression analysis. The findings reveal a significant difference between users and non-users of MOOCs in their intentions to use MOOCs for academic purposes. It again indicated that all predictor variables significantly contribute to the prediction of intention to use MOOCs for academic purposes except how-to knowledge and actual usage. It also reveals that students’ intention to use MOOCs for academic purposes is raised by the perceived usefulness which reflects in their attitude. Awareness knowledge, in turn, incline the perceived usefulness of MOOCs to students signifying that a substantial amount of knowledge of MOOCs is a precursor to a higher level of intention to use..